Análise dos efeitos da potencialização pós-ativação na velocidade em atletas de atletismo - Souza, Kennedy Anderson Lima (2017)
The goal of this study was to analyze the influence of post-activation potentiation (PAP) in college athletes through one maximum repetition on squat on various performance tests. Five college long jump athletes of age between 18 and 30 years old were selected, all of them federate track and field athletes of CBAT (Brazilian Athletics Confederation), and affiliated to the team CEUC-UFC. The tests were offered in 2 sessions during the period of 1 week. For performance comparison were used a 20 meters speed test and one maximum repetition test. The tests and data collection were conducted in 2 sessions, at two different moments: the first moment without the use of PAP and the second moment with the use of PAP. In the first data collection session (T1) was held the 20 meters speed test and later the one maximum repetition test. Between a period of 24 to 48 hours after T1 was held the T2, collecting performance values on the speed test. Statistical analysis was calculated using a difference in average 5% (effect size) and also standard deviation equal to 5%, both obtained in preliminary experiments and literature, by adjusting the power of the statistical test for 0.8 and the alpha error to 0.05. Results showed that in track and field athletes there was a 2.5% increase in speed at the 20 meters test, with a 5.2% decrease in time to run the same distance. Therefore, PAP has proven an effective mechanism to increase the performance of long jump athletes.